2020
DOI: 10.1038/s41545-020-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Water supply and sanitation services in small towns in rural–urban transition zones: The case of Bushenyi-Ishaka Municipality, Uganda

Abstract: Small towns lag behind cities in drinking water and sanitation access globally. Closing this gap requires developing service models for areas with both urban and rural characteristics. This study assessed Bushenyi-Ishaka, a municipality in Uganda situated at the rural–urban transition, with a focus on service ladder indictors. Data sources included household interviews (n = 500) and water quality samples from sources and storage containers. Households in more urban (as compared to rural) cells were more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 10 publications
2
45
0
1
Order By: Relevance
“…The most frequently identified risks regarding household practices were the use of multiple water sources (100%) and inadequate coverage of the final storage container, i.e., the container from which drinking water is directly accessed by household members (80%) ( Table 2). This is consistent with a previous study in the same area that found households dealt with unreliable, seasonal, or costly water supplies by using multiple sources [22]. There were almost no risks identified in bulk storage containers, i.e., intermediate containers used between collection and final storage, while many potential risks were found for collection and the final storage containers.…”
Section: Sanitary Inspectionsupporting
confidence: 90%
See 4 more Smart Citations
“…The most frequently identified risks regarding household practices were the use of multiple water sources (100%) and inadequate coverage of the final storage container, i.e., the container from which drinking water is directly accessed by household members (80%) ( Table 2). This is consistent with a previous study in the same area that found households dealt with unreliable, seasonal, or costly water supplies by using multiple sources [22]. There were almost no risks identified in bulk storage containers, i.e., intermediate containers used between collection and final storage, while many potential risks were found for collection and the final storage containers.…”
Section: Sanitary Inspectionsupporting
confidence: 90%
“…The piped water supply system is managed by the National Water and Sewerage Corporation (NWSC), which is owned and operated by the national government. This study is the continuation of a previous water and sanitation study conducted in the same area [22], which reported that almost half of the households relied on protected springs (48%) as their main drinking water source, followed by unprotected springs (20%), and piped supply (18%) [22]. About one in five households had their water source located on-plot.…”
Section: Study Areasupporting
confidence: 59%
See 3 more Smart Citations